High-harmonic generation in two-dimensional semiconductors - Gadermaier, Christoph (Frontiers in Nanotechnology, 2026)
High-harmonic generation has been established in gases both as a source of extreme ultraviolet light as well as a tool for studying atomic and molecular physics in the attosecond time domain. The more recent extension of these methods to condensed matter affords much higher conversion efficiencies and offers an even richer selection of accessible phenomena. Atomically thin two-dimensional semiconductors combine mechanical robustness with intriguing many-body physics and exceptionally strong light-matter interaction. This mini-review gives a glance into the high-harmonic generation mechanisms in two-dimensional semiconductors, with particular emphasis on symmetry considerations, many-body effects, photodoping, and techniques to further enhance the high-harmonic generation efficiency.